Bio-monitoring for atmospheric nitrogen pollution using epiphytic lichens and bryophytes - Lewis, Jason Edward James (2012)
Nitrogen enrichment in sensitive habitats has become a matter of concern in recent years, and has led to the need to develop a bio-monitoring scheme that could be used by non-specialists to undertake site evaluation across the UK. Epiphytes are ideal candidates for such a project due to their high sensitivity to atmospheric pollutants. Indicator species analysis identified a comprehensive UK-specific list of epiphytic indicators for NH3 pollution in the UK that for the first time also included microlichens. A shortlist of easily identifiable, widely distributed indicator species was produced from these and used to trial the effectiveness of a frequency based scoring system. A simple, un-weighted frequency based scoring system founded on the Lichen Acidophyte Nitrophyte index was found to correlate strongly with NH3 concentrations in air. Assessment of other atmospheric chemistry and climate variables with the scoring system showed that NO2 concentrations in air and bark pH were confounding factors. The influence of pH was further validated by observations in a field experimentation plot where different N forms were applied. In order to address this, a regression equation was formulated that incorporated NH3, NO2 and bark pH to produce a predictive model that could potentially be used to evaluate site condition with respect to atmospheric N pollution, as defined by the combined effect of NH3 and NO2. Investigations into the biochemistry of an indicator species identified that rates of phosphomonoesterase (PME) activity were higher in N-sensitive species than N-tolerant ones. N-sensitive lichen thallus pH measurements for were also consistently more acidic than those of N-tolerant species, and closer to the observed pH optima of PME activity.